Manajemen Pendidikan Inklusi dalam Penanaman Karakter Tanggung Jawab pada Mata Pelajaran PPKn di SMP - Putri, Ayu Fitri S.; Harmanto, Harmanto (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2020)
This research intention to understand the implementation of inclusive education management in instilling the character of responsibility in inclusive classes in SMP Negeri 4 Sidoarjo. Aspects observed in the implementation of character education include learning, example, reinforcement, and habituation. This research is a qualitative study with case study type. Subject research (key informant) was the VII grade PPKn teacher. The research setting took place in class VII of SMP Negeri 4 Sidoarjo. Data collection method used were observation, best interviews and study of documentation. we analyze data steps of reduction, presentation, and drawing conclusions. Data validity checking techniques using triangulation techniques and sources. The results indicate that the VII grade teachers of SMP Negeri 4 Sidoarjo had instilled the values of responsibility character in students in their class through citizenship learning. In the implementation of citizenship learning, the teacher emphasizes the inculcation of the value of the character of responsibility. This is done by the teacher in learning by implanting concepts through explanations, discussing moral issues, stories, active learning, and methods of cooperation between students. Teachers also provide role models in attitudes and actions, give appreciation, provide individual assistance and familiarize students with each other with friends who have special needs, both in the classroom and outside the classroom.